Robust design of a polygonal shaft-hub coupling (Fracture and Structural Integrity, 2015)
In this work, the Taguchi method is applied for the optimal choice of design parameter values for a polygonal shaft-hub coupling. The objective is to maximize a performance function, minimizing, at the same time, its sensitivity to noises factors (robust design). The Design of Experiments (DoE) is adopted to set up a plan of numerical experiments, whose different configurations are simulated using the Boundary Element Method (BEM).
Keywords: Polygonal shaft-hub coupling